Po’s Pursuit of Personal Transformation in Tracey West’s Kung Fu Panda 3 - Wicaksono, Satrio; Wahyono, Danu (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2025)
This research explores the multidimensional process of personal transformation experienced by the protagonist, Po, in Kung Fu Panda 3 by Tracey West. The study aims to examine Po’s internal development by focusing on his identity struggle, emotional maturation, and spiritual awakening as he transitions from a self-doubting warrior to a fully realised leader. Employing a qualitative research method, this study conducts a close reading and thematic analysis of the novel to uncover the psychological layers of Po’s transformation. The research highlights that Po’s evolution is not merely defined by physical prowess or heroic feats, but is deeply rooted in his internal reconciliation and personal growth. The findings reveal that Po’s personal transformation unfolds through three primary dimensions: psychological, emotional, and spiritual. Psychologically, Po confronts an identity crisis sparked by his sudden role as a teacher and the discovery of his biological father. His internal struggle between who he thinks he should be and who he authentically is forms the core of his psychological fragmentation. Emotionally, Po grapples with loyalty and guilt as he navigates his relationships with both his adoptive father, Mr. Ping, and his biological father, Li Shan. These emotional challenges push Po toward a deeper sense of empathy, emotional regulation, and maturity. Spiritually, Po’s journey culminates in his mastery of chi, a symbolic act of inner harmony and self-acceptance, reflecting his attainment of a fully integrated self. Keywords: Emotional Growth, Identity Crisis, Personal Transformation, Self-Acceptance, Spiritual Awakening